The Chimpanzees of bossou and nimba - Matsuzawa, Tetsuro. (Springer Japan, 2011)
The chimpanzees of Bossou in Guinea, West Africa, form a unique community which displays an exceptional array of tool use behaviors and behavioral adaptations to coexistence with humans. This community of Pan troglodytes verus has contributed more than three decades of data to the field of cultural primatology, especially chimpanzees’ flexible use of stones to crack open nuts and of perishable tools during foraging activities. The book highlights the special contribution of the long-term research at Bossou and more recent studies in surrounding areas, particularly in the Nimba Mountains and the forest of Diécké, to our understanding of wild chimpanzees’ tool use, cognitive development, lithic technology and culture. This compilation of research principally strives to uncover the complexity of the mind and behavioral flexibility of our closest living relatives. This work also reveals the necessity for ongoing efforts to conserve chimpanzees in the region. Chimpanzees have shed more light on our evolutionary origins than any other extant species in the world, yet their numbers in the wild are rapidly declining. In that sense, the Bossou chimpanzees and their neighbors clearly embody an invaluable cultural heritage for humanity as a whole.          Readers can enjoy video clips illustrating unique behaviors of Bossou chimpanzees, in an exclusive DVD accompanying the hardcover or at a dedicated website described in the softcover. Part 1: introduction -- 1 Bossou: 33 years -- Part 2: history and ecology -- 2 Location and ecology -- 3 The demography and reproductive parameters of Bossou Chimpanzees -- 4 The “prehistory” before 1976: looking back on three decades of research on Bossou Chimpanzees -- 5 The chimpanzees of West Africa: from “man-like beast” to “our endangered cousin” -- Part 3: culture: tool manufacture and use -- 6 The tool repertoire of Bossou chimpanzees -- 7 Stone tools for nut-cracking -- 8 Use of leaves for drinking water -- 9 Ant-dipping: how ants have shed light on culture -- 10 Pestle-pounding behavior: the key to the coexistence of humans and chimpanzees -- 11 Algae scooping remains a puzzle -- 12 Ant fishing in trees: invention and modification of a new tool-use behavior -- 13 Log doll: pretence in wild chimpanzees -- 14 Animal toying -- Part 4: stone tool use: observation and experiments -- 15 Extensive surveys of chimpanzee stone tools: from the telescope to the magnifying glass -- 16 Field experiments of tool-use -- 17 Clues to culture? the coula- and panda-nut experiments -- 18 From handling stones and nuts to tool-use -- 19 The emergence of stone-tool use in captive chimpanzees -- 20 A gibsonian motor analysis of the nut-cracking technique -- 21 Education by master-apprenticeship -- Part 5: Social life and social intelligence -- 22 The crop-raiders of the sacred hill -- 23 Behavioral flexibility and division of roles in chimpanzee road-crossing -- 24 Play behaviors involving the use of objects in young chimpanzees at Bossou.-25 Chimpanzee mothers carry the mummified remains of their dead infants: three case reports from Bossou -- 26 Comparison of social behaviors -- Part 6: Adjacent communities -- 27 The chimpanzees of Yealé, Nimba -- 28 Chimpanzees in the Seringbara region of the Nimba mountains -- 29 Chimpanzees in the eastern part of the Nimba mountains biosphere reserve: Gouéla II and Déré forest